FREQUENCY OF LEFT VENTRICULAR DIASTOLIC DYSFUCTION IN END STAGE RENAL DISEASE PATIENTS ON HEMODIALYSIS - Ahmed, Raheel; Munib, Syed; Ahmed, Tausif (Pakistan Journal of Kidney Diseases, 2023)
INTRODUCTION: Cardiovascular diseases represent the main cause of morbidity and mortality in patients with chronic kidney disease (CKD. Left ventricular hypertrophy (LVH) represents a key feature to provide an accurate picture of systolic-diastolic left heart involvement in CKD patients. OBJECTIVE: To determine the frequency of left ventricular diastolic dysfunction in end stage renal disease patients on hemodialysis. Material and Methods: Descriptive Cross Sectional was conducted at Department of Nephrology, Institute of Kidney Diseases Peshawar from 11th July 2018 to 10th January All the patients were stabilized and after initial stabilization and treatment of these patients, written informed consent was obtained from them. Echocardiogram was performed by consultant cardiologist in order to look for the presence of LV dysfunction. LV systolic dysfunction considered depressed when left ventricular ejection fraction (LVEF) was found less than 45%. Clinical and electrocardiographic evidences of valvular heart disease, heart failure (EF<50%) and myocardial ischemia were excluded from this study. RESULTS: As per frequencies and percentages for LVDD, 121 (87.68%) patients were recorded with LVDD. CONCLUSION: In this study, we concluded that LVDD is a typical feature of CKD-related cardiomyopathy as LVDD and myocardial fibrosis are associated with mortality risk and cardiovascular events in CKD and ESRD as demonstrated by higher rates of sudden cardiac death in these patients.